Rogues Among Rebels: Entanglements between Irish Catholics and the Fishermen’s Protective Union of Newfoundland - O'Flaherty, Liam Michael (Simon Fraser University, 2017)
This thesis explores the relationship between Newfoundland’s Irish Catholics and the largely English-Protestant backed Fishermen’s Protective Union (FPU) in the early twentieth century. The rise of the FPU ushered in a new era of class politics. But fishermen were divided in their support for the union; Irish-Catholic fishermen have long been seen as at the periphery—or entirely outside—of the FPU’s fold. Appeals to ethno-religious unity among Irish Catholics contributed to their ambivalence about or opposition to the union. Yet, many Irish Catholics chose to support the FPU. In fact, the historical record shows Irish Catholics demonstrating a range of attitudes towards the union: some joined and remained, some joined and then left, and others rejected the union altogether. Far from being beholden to the whims of clerics, political elites, or the structural dictates of the economy and of region, Irish-Catholic fishermen made their own decisions about membership. Nevertheless, the pressures of class and ethno-religious solidarities mediated their decisions to engage with the union. This thesis uses a combination of newspaper sources, church correspondence, oral histories, censuses, and election data to unearth the history of Irish Catholics’ complex relationship with the FPU, and argues that this relationship is an example of the entanglements of ethnicity and class in pre-Confederation Newfoundland.